Kill Bill. Volume 2 [videorecording (Blu-Ray)] - Thurman, Uma; Carradine, David; Liu, Lucy, 1968-; Fox, Vivica A., 1964-; Madsen, Michael; Hannah, Daryl; Liu, Chia Hui; Parks, Michael, 1940-2017 (Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2008)
The Bride continues on her deadly pursuit of her former partners in the Deadly Viper Assassination Squad, who, in a furious assault, attempted to murder her and her unborn child on her wedding day. As the Bride faces off against allies-turned-nemeses Budd and Elle, she flashes back to the day of her deadly wedding. We learn how she was recruited and trained and about her relationship with Squad leader Bill.